Coral reefs at Qiziwan National Marine Park in 2023: spatial variability and their relationship with environmental factors - Zhao, He; Zhang, Junling; Yang, Haijun; Li, Yiping; Liu, Xiangbo; Liu, Yicheng; Zhu, Wentao; Wang, Aimin; Li, Xiubao (Frontiers in Marine Science, 2024)
he marine environmental variables, coral communities, and ecosystem parameters were surveyed at Qiziwan National Marine Park (QZW) in 2023 at 19 sampling stations, which spread among four regions: Xiaojiao Park, Zhongjiao Park, Dajiao Park, and Shayutang Village. The survey identified 67 species of reef-building corals belonging to 25 genera. The dominant coral species included Porites lutea, Goniopora columna, Platygyra sinensis, Favites flexuosa, Galaxea fascicularis, and Acropora millepora. At Xiaojiao Park, the coral coverage was low, and the water had high levels of turbidity and dissolved inorganic nitrogen, likely due to the impact from the nearby Changhua Port. Dajiao Park was unsuitable for coral survival because its substrate was dominated by sand. Zhongjiao Park and Shayutang Village had the best coral ecosystems. Redundancy analysis revealed that turbidity and substrate types were significant environmental factors that influenced coral distribution. The coverage of live corals at Xiaojia Park, partial positioning of Zhongjiao Park and Dajiao Park declined from 14.03% in 2017 to 11.73% in 2023, potentially due to frequent marine construction and land use changes. Anthropogenic disturbances may have worsened environmental conditions and undermined the survival of coral reefs at QZW.